Books: Evaluative research methods. Managing the complexities of judgment in the field: Evaluation for Social Justice - Greenhalgh, T (Royal College of General Practitioners, 2017)
Book review of: "Evaluative research methods. Managing the complexities of judgment in the field", Saville Kushner, Information Age Publishing, Inc. 2017, PB, 296pp, £37.80, 978-1681236889